Brain behavioral systems, self-control and problematic mobile phone use: The moderating role of gender and history of use. (1st February 2017) - Jiang, Zhaocai; Zhao, Xiuxin
Abstract: Problematic mobile phone use is getting increasing attention due to the popularity of mobile phone in recent years. The current study investigated 468 college students to explore the roles of the behavioral activation system (BAS), behavioral inhibition system (BIS) and self-control in problematic mobile phone use. Gender was found to moderate the relationship between BIS and problematic mobile phone use with decreased BIS associated with greater problematic cell phone use for males, but not females. For females, excessive mobile phone use was predicted by self-control and moderated by time since acquisition of mobile phone. That is, for high self-control females, the level of problematic mobile phone use was decreased as time to own mobile phone becomes longer, yet for low self-control counterparts the correlation was reversed. Our research provides evidence for the close association between BIS/self-control and problematic mobile phone use, indicating the critical moderating roles of gender and history of use in these links. Highlights: Negative association between BIS and problematic mobile phone use was found for males, not for females. For females, problematic mobile phone use was predicted by self-control and moderated by use history. Phone overuse correlated negatively with use history for high self-control females, yet positively for low self-controllers.